Modernity and postmodernity : knowledge, power and the self - Delanty, Gerard (SAGE Publications, 2000)
This accessible and comprehensive overview of the main issues on the modernity-postmodernity controversy is the first clear-sighted book on the subject. It surveys modern social theory, from Kant to Weber with economy and masterly precision. And evaluates the work of the Frankfurt School, Arendy, Strauss, Luhmann, Habermas, Heller, Castoriadis and Touraine, before moving on to consider the approaches of the leading writers on postmodenrity: Lyotard, Vattimo, Derrida, Foucault and Jameson.